A new genus in the tribe Bothriocerini (Hemiptera: Auchenorrhyncha: Fulgoroidea: Cixiidae) from the cloud forests of Costa Rica, a key to genus, and an updated molecular phylogeny - Barrantes, Edwin A. Barrantes; Echavarria, Marco A. Zumbado; Vega, Jefferson Orozco; Chaves, Birgid Montero; Bartlett, Charles R.; Bahder, Brian W. (Zootaxa, 2025)
A recent survey of planthoppers on palms (Arecaceae) in Costa Rica found a new genus of Cixiidae (Bothriocerini), described here as Circumdara gen. nov., with two new species, C. cidicera gen. et sp. nov. and C. nela gen. et sp. nov., from palms in the Los Angeles cloud forest. They are described with supplemental molecular data for the cytochrome c oxidase subunit I (COI), histone 3 (H3), 18S rRNA and D8–D10 expansion regions of 28S rRNA genes. The molecular data are analyzed to provide an updated phylogeny for the Bothriocerini relative to the Oecleini.